The Role of Self-Efficacy and Locus of Control in Enhancing Employee Performance at Aceh Culture and Tourism Office - Syarifah Mauli Masyithah; Teuku Muhammad Syauqi; Nurrahmad Nurrahmad; Sisca Mediyanti; Leni Marlina; Syafira Yunidar; Awwaliah Awwaliah (Journal Economic Management and Business, 2026)
This research aims to examine the influence of self-efficacy and locus of control on employee performance at the Aceh Culture and Tourism Office. The research was motivated by the suboptimal performance of employees, which is presumed to be associated with individual psychological factors, particularly self-efficacy and locus of control. A quantitative approach with an associative research design was employed in this research. The population consisted of 249 employees of the Aceh Culture and Tourism Office, while 71 respondents were selected as samples using the Slovin sampling method. Data were collected through questionnaires using a Likert scale to measure self-efficacy, locus of control, and employee performance. The collected data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The findings indicate that self-efficacy has a positive effect on employee performance. In addition, locus of control also positively influences employee performance. Meanwhile, both self-efficacy and locus of control contribute significantly to improving employee performance. The research concludes that psychological factors play an important role in enhancing employee performance in the public sector. Organizations should strengthen employees’ self-confidence and promote positive self-control to improve work effectiveness and productivity.